ANALISIS STRATEGI PEMBELAJARAN SEJARAH DI ERA DIGITAL: KAJIAN LITERATUR SISTEMATIS - Fadhilah Fadhilah; Syarfira Syarfira; Muhammad Bagas Hidayatuallah; Syarifuddin Syarifuddin; Rani Oktapiani (Universitas Jabal Ghafur, 2026)
The development of digital technology has driven significant transformation in history learning, requiring innovative and adaptive learning strategies to meet modern educational demands. This study aimed to analyze history learning strategies in the digital era through a systematic literature review of national and international scientific articles published from 2021 to 2025. The research method used a systematic literature review by selecting and analyzing relevant studies related to technology-based history learning. The results showed that project-based learning, problem-solving, inquiry learning, digital storytelling, and the use of interactive digital media effectively improve historical thinking skills, digital literacy, creativity, and student learning motivation. In conclusion, history learning in the digital era requires strengthening educator competence, technological infrastructure support, and sustainable learning innovation to become more effective and relevant. Keywords : history learning, digital era, digital strategy, digital literacy, educational technology